Discerning the subfibrillar structure of mineralized collagen fibrils: a model for the ultrastructure of bone. - Yuping Li (Public Library of Science (PLoS), 2013)
Biomineralization templated by organic molecules to produce inorganic-organic nanocomposites is a fascinating example of nature using bottom-up strategies at nanoscale to accomplish highly ordered multifunctional materials. One such nanocomposite is bone, composed primarily of hydroxyapatite (HA) nanocrystals that are embedded within collagen fibrils with their c-axes arranged roughly parallel to the long axis of the fibrils. Here we discern the ultra-structure of biomimetic mineralized collagen fibrils (MCFs) as consisting of bundles of subfibrils with approximately 10 nm diameter; each one with an organic-inorganic core-shell structure. Through an amorphous calcium phosphate precursor phase the HA nanocrystals were specifically grown along the longitudinal direction of the collagen microfibrils and encapsulated them within the crystal lattice. They intercalated throughout the collagen fibrils such that the mineral phase surrounded the surface of collagen microfibrils forming an interdigitated network. It appears that this arrangement of collagen microfibrils in collagen fibrils is responsible for the observed ultrastructure. Such a subfibrillar nanostructure in MCFs was identified in both synthetic and natural bone, suggesting this is the basic building block of collagen-based hard tissues. Insights into the ultrastructure of mineralized collagen fibrils have the potential to advance our understanding on the biomineralization principles and the relationship between bone's structure and mechanical properties, including fracture toughness mechanisms. We anticipate that these principles from biological systems can be applied to the rational design of new nanocomposites with improved performance.